2014
DOI: 10.1186/s12967-014-0290-2
|View full text |Cite|
|
Sign up to set email alerts
|

A randomised translational trial of lifestyle intervention using a 3-tier shared care approach on pregnancy outcomes in Chinese women with gestational diabetes mellitus but without diabetes

Abstract: BackgroundThere are no randomised controlled trials to demonstrate whether lifestyle modifications can improve pregnancy outcomes of gestational diabetes mellitus (GDM) diagnosed by the International Association of Diabetes and Pregnancy Study Group’s (IADPSG) criteria. We tested the effectiveness of lifestyle modifications implemented in a 3-tier’s shared care (SC) on pregnancy outcomes of GDM.MethodsBetween December 2010 and October 2012, we randomly assigned 700 women with IADPSG-defined GDM but without dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
104
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(107 citation statements)
references
References 34 publications
2
104
1
Order By: Relevance
“…In the present study, there was no differences between the two groups in terms of delivery type. For other interventions, no differences were found in maternal and obstetric outcomes such as maternal hospitalization days, type of delivery, postpartum complications, and rates of cesarean delivery . The high prevalence of previous cesarean delivery in the present study may explain why there was no significant difference in delivery type between the two groups.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…In the present study, there was no differences between the two groups in terms of delivery type. For other interventions, no differences were found in maternal and obstetric outcomes such as maternal hospitalization days, type of delivery, postpartum complications, and rates of cesarean delivery . The high prevalence of previous cesarean delivery in the present study may explain why there was no significant difference in delivery type between the two groups.…”
Section: Discussioncontrasting
confidence: 58%
“…In the present study, a number of important neonatal outcomes, such as Apgar scores in the 1st and 5th min after birth and hospitalization of newborns, were significantly better in the intervention group. Numerous studies have reported that self‐care educational interventions have a significant effect on neonatal outcomes, such as infant hospitalization, Apgar score < 7, preterm delivery, and birth weight . However, other studies indicate that there is no difference in neonatal hospitalization days, birth weight, admission to the neonatal intensive care unit neonatal complications and death, and preterm labor after self‐care educational intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our indings agree with those of [14] which showed that lifestyle modi ication improved pregnancy outcome in Chinese women with GDM. An important fact that needs to be noted is the high incidence of admission of the babies with hyperbillirubenimea to NICU in comparison to previously studied years in our hospital & other institutes.…”
Section: Discussionsupporting
confidence: 92%
“…Among 1378 women with GDM diagnosed by IADPSG's criteria, 853 women ( N = 427 in the assigned shared care (SC, i.e. intensive lifestyle intervention) group and N = 426 in the assigned UC group) participated in a randomized controlled translational trial . However, due to logistic reasons, 108 women in the assigned UC group during Nov 2010 to July 2011 might have received unintentional intervention, subject to potential contamination.…”
Section: Methodsmentioning
confidence: 99%